Community-level management of bio-resources for augmenting income from coconut-based farming systems in Kerala state, India - Kalavathi, S.; Mathew, Jeena; Indhuja, S.; Babu, Merin; Muralidharan, K. (Journal of Plantation Crops, 2020)
On-farm management of farm residues for mass multiplication of beneficial microbes plays an important role in organic farming as well as integrated nutrient management by improving soil health. Community-level production of organic inputs from crop residues can be a potential source of income for farmers’ groups also. A large scale operational research on community-based bio-resource management, along with soil test based nutrient management, was undertaken by ICAR-CPCRI with financial support from NABARD in the major organic tract of Kerala in the coastal belt - Kanjikuzhy block during 2014-2016. The bio-resource management components under technology integration included farm-level production of organics from crop residues, enrichment using bio-agents, utilization of enriched organics for soil and plant health management and production of bio-primed planting materials. For enhancing the efficiency of Trichoderma-enriched organic manure, two ideal media viz., coir pith compost + neem cake (4:1) and coir pith compost + neem cake + poultry manure + cow dung (2:1:1:1) were standardized. Coconut seedlings produced through bio-priming with Trichoderma sp. showed early germination (90%), higher recovery percentage (79.5%), higher collar girth (17 cm), more number of fronds (9) and height (160 cm). Farm-based participatory action management integrating cost-effective bio-resource management interventions in coconut-based farming systems resulted in improvements in income from coconut by 26 per cent and intercrops by 142.9 per cent, contributing to an increase in the average farm income by 149.8 per cent. The average knowledge index of the respondents related to bio-resource management increased by 115.8 per cent and that of integrated nutrient management by 74.5 per cent.